Output and Employment Generated in the Malaysian Manufacturing Sector: An Input-Output Analysis - Mohd Khairul Hisyam, Hassan; Baharom, A.H; Khairunnisa, Abd Azis (Global Strategic Management, Inc., 2010)
This study was conducted to examine the effects of export changes on the output and employment in the manufacturing sector. Specifically, this study aimed to (1) measure the level of output generated due to changes in export to ASEAN 4;(2) estimate the level of employment generated due to changes in export to ASEAN 4.(3) analyze which country among ASEAN 4, namely Indonesia, Philippines, Thailand and Singapore is the most important destination of Malaysian manufacturing exports.The period of study covers the time period 2000-2004. We employed the Input Output (IO) method since structural analysis deals with economic systems as defined by the set of industries and the relationships between them. However, multi-sectoral models are often limited: when studying economic systems empirically it is difficult to distinguish a priori the subset of basic or important relationships between industries. There are positive relationship for manufacturing export and output and employment. Export increased rapidly within this five years leading to output and employment growth of 23% and 37% respectively. Analysis in 2004 showed that spending of every RM1 of export to Indonesia generated output of RM1.28, while RM 1.26 was generated by Philippines, RM 1.25 by Thailand and RM1.23 by Singapore.